Neural correlates and plasticity of explicit emotion regulation following the experience of trauma - Konrad, Annika C.; Miu, Andrei C.; Trautmann, Sebastian; Kanske, Philipp (Frontiers in Behavioral Neuroscience, 2025)
Experiencing trauma or other adverse life events is highly prevalent and poses a significant risk for the development of mental disorders. Understanding the underlying mechanisms and neural processes involved in trauma processing is crucial for both prevention and targeting symptoms. Especially, difficulties in emotion regulation emerge as one key mechanism implicated in the development of conditions such as post-traumatic stress disorder (PTSD) following traumatic experiences. However, neural correlates of explicit emotion regulation among individuals who have undergone trauma have not received much attention. Understanding the neural basis of dysregulated emotion following trauma could reveal important details about how trauma interferes with emotional regulation systems, informing the development of more specific intervention approaches. Therefore, this mini review summarizes current research, and identifies relevant gaps in the literature and challenges for future studies. Specifically, it provides an overview of the neural dysregulation associated with explicit emotion regulation strategies such as reappraisal or suppression. Finally, it highlights promising findings from intervention studies targeting emotion regulation, such as trauma-focused exposure therapy and neurofeedback, indicating neural plasticity in individuals with traumatic experiences. Hereby, this review aims to bridge the gap between fundamental and intervention research and highlights future directions for translational research.